THE IMPACT OF STUDENT PARTICIPATION IN ENVIRONMENTAL EDUCATION PROGRAMS ON PRO-ENVIRONMENTAL BEHAVIOR - Julia Anis Handayani; Ari Widodo (Universitas Majalengka, 2024)
The low awareness and behaviour of environmental care and the increasing cases of environmental damage caused by human behaviour are the background of the research. Environmental problems caused by humans continue to occur and increase every year, ranging from the destruction of ecosystems to the emergence of waste that damages the environment. Environmental care behaviour is an important part that must be owned by every human being on earth, because this is related to the survival of every creature, both plants, animals, and other humans. This study aims to determine the effect of students' participation in environmental education programmes on pro environmental behaviour. This research is a type of quantitative research with survey method. Data collection techniques were obtained by means of observation and questionnaires. The research subjects were 5th grade elementary school students totalling 45 people. Data analysis was conducted using paired sample t test to measure the influence between variables and linear regression analysis to measure the amount of influence given. The results showed that there was a positive influence of student participation on pro environmental behaviour with sig. 0.004 < 0.005, with rcount = 0.419 > rtable = 0.294 so that it can be interpreted that the higher the participation of students in the environment, the better the environmental care behaviour, where R2 = 0.175 shows the influence of student participation with pro environmental behavior by 17%, while 83% is influenced by other factors. From these results, it shows that students' participation in environmental education programs plays an important role in supporting environmental care behaviour that leads to attitudes to protect the environment. The implication of the research is as a database and evaluation of education, especially in the environmental care behaviour of elementary school students.